Warenhuis As a National Cultural Heritage Site A Legacy of The Dutch Colonial Era In Medan - N Najuah; Fitri Nurjihan; Dania Amanda; Esa Indriyani Br Bangun; Lutfia Khairani Pane (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
At the beginning of its development, Medan City was a small village called